2018
DOI: 10.1038/s41593-017-0050-8
|View full text |Cite
|
Sign up to set email alerts
|

Hexadirectional coding of visual space in human entorhinal cortex

Abstract: Entorhinal grid cells map the local environment, but their involvement beyond spatial navigation remains elusive. We examined human functional MRI responses during a highly controlled visual tracking task and show that entorhinal cortex exhibited a sixfold rotationally symmetric signal encoding gaze direction. Our results provide evidence for a grid-like entorhinal code for visual space and suggest a more general role of the entorhinal grid system in coding information along continuous dimensions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
204
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 177 publications
(232 citation statements)
references
References 20 publications
28
204
0
Order By: Relevance
“…Computational models proposed that it is the conjunction between location and direction that mediates the environmental anchoring of HD in the RSC (Bicanski and Burgess, 2016). In monkeys (Killian et al, 2015) and humans (Julian et al, 2018;Nau et al, 2018cNau et al, , 2018aStaudigl et al, 2018), eye movement direction has also been shown to modulate activity in the entorhinal cortex in which we also observed a directional code. However, these studies focused on eye movements in the 2D plane (e.g.…”
Section: Influence Of Gaze Directionsupporting
confidence: 69%
“…Computational models proposed that it is the conjunction between location and direction that mediates the environmental anchoring of HD in the RSC (Bicanski and Burgess, 2016). In monkeys (Killian et al, 2015) and humans (Julian et al, 2018;Nau et al, 2018cNau et al, , 2018aStaudigl et al, 2018), eye movement direction has also been shown to modulate activity in the entorhinal cortex in which we also observed a directional code. However, these studies focused on eye movements in the 2D plane (e.g.…”
Section: Influence Of Gaze Directionsupporting
confidence: 69%
“…Kilian et al (2012) discovered cells within the entorhinal cortex of macaques that coded the location of fixations in a grid-like fashion during a free-viewing task, serving as a potential mechanism to provide a scale-invariant representation of fixation locations within the scene (Bicanski and Burgess, 2019). Similar grid-like modulation of entorhinal activity has been observed in humans using fMRI (Julian et al, 2018;Nau et al, 2018), providing converging evidence across species that the entorhinal system may provide a spatial framework for memory-guided viewing. As such, synchronous theta oscillations between the hippocampus and entorhinal systems would provide the spatial coding necessary to inform the oculomotor system of memory-relevant information.…”
Section: Discussionmentioning
confidence: 87%
“…110,111 Likewise, in humans, the ERC responses code for gaze direction in a grid-like fashion. 112 Neurons in the monkey PHC and hippocampus are also responsive to the spatial locations of gaze fixations, 104,[113][114][115][116][117][118] likely according to allocentric reference frames. 119 In both monkeys and humans, theta rhythm is aligned with saccades during a visual search task ( Fig.…”
Section: Neurophysiology and Oscillatory Responsesmentioning
confidence: 99%